Comparison of peripheral artery plaque characteristics between ACS patients with plaque rupture and plaque erosion in culprit coronary artery: an OCT and ultrasound study. (14th October 2021) - Weng, Z Q; Hu, S N; Zhao, C; Qin, Y H; Feng, X; He, L P; Xu, Y S; Yu, H; Ren, X F; Hou, J B; Jia, H B; Yu, B
Abstract: Background: Recent research has found that the characteristics of peripheral arterial plaque are related to the increased risk of cardiovascular disease, however, the relationship of plaque characteristics between peripheral artery and coronary is still unknown. Purpose: To assess the correlation between coronary plaque characteristics assessed by optical coherence tomography (OCT) and peripheral artery plaque characteristics assessed by ultrasound. Methods: 150 patients with acute coronary syndrome (ACS) underwent coronary angiography were prospectively enrolled. OCT imaging of culprit vessel were performed during the procedure and ultrasound examination of bilateral carotid, iliofemoral and popliteal arteries was performed during hospitalization after procedure. Panvascular disease was defined as the presence of observable plaques in two or more vascular beds. Patients were divided into plaque rupture (PR) group and plaque erosion (PE) group according to culprit plaque characteristics on OCT. Results: There were 132 (88%) ACS patients had panvascular disease in which 36 (24%) with generalized atherosclerosis (4 sites) and the prevalence of panvascular atherosclerosis in PR group was significantly higher than in PE group especially in carotid arteries and iliofemoral arteries (Figure 1, Figure 2). Compared to PE group, PR group had higher carotid plaque score (p=0.001) which indicates more plaques and severer atherosclerosis. Moreover, there were larger intima-media thickness (IMT) of iliofemoral arteries (6.9±1.4mm vs. 6.5±1.1mm, p=0.036) and more calcified plaques in PR group. Conclusions: Panvascular disease is highly prevalent in ACS patients especially in patients with plaque rupture in culprit vessel, in which more than half of the patients had plaques in more than 3 sites of vascular beds. In addition, patients with plaque rupture had thicker iliofemoral IMT and higher panvascular atherosclerosis burden, which indicates that characteristics of coronary plaques are the focal expression of plaques in the whole panvcascular system. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Key R&D Program of China